2015
DOI: 10.1021/acs.inorgchem.5b01064
|View full text |Cite
|
Sign up to set email alerts
|

A Stable Planar-ChiralN-Heterocyclic Carbene with a 1,1′-Ferrocenediyl Backbone

Abstract: This paper focuses on the stable, ferrocene-based N-heterocyclic carbene (NHC) rac-[Fe{(η(5)-t-BuC5H3)NpN}2C:] (A'-Np, Np = neopentyl), which is planar-chiral due to the two tert-butyl substituents in 3,3'-positions. A'-Np was synthesized in nine steps starting from 1,1'-di-tert-butylferrocene (1), the first step being its 3,3'-dilithiation to afford rac-[Fe(η(5)-t-BuC5H3Li)2] (rac-fc'Li2, 2). The structures of rac-fc'(SiMe3)2 (3), rac-fc'Br2 (4), rac-fc'(N3)2 (5), and the immediate carbene precursor [A'-NpH]B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 51 publications
(31 citation statements)
references
References 85 publications
1
30
0
Order By: Relevance
“…DFT calculations indicate an appreciable delocalisation of the charge and spin density onto the carbene centre for the oxidised form . Nevertheless, the large anodic shift of the E 1/2 value by 0.410 V in 1′Np C relative to the corresponding 3,3′‐di‐ tert ‐butyl‐1,1′‐bis(neopentylamino)ferrocene precursor ( E 1/2 =−0.720 V) indicates sizable electron donation of the amino substituents to the carbene carbon atom, thus rendering oxidation less facile . With the availability of the present new compounds, it was of great interest to study the effect of the nature of the divalent tetrel atom on the electrochemical properties.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…DFT calculations indicate an appreciable delocalisation of the charge and spin density onto the carbene centre for the oxidised form . Nevertheless, the large anodic shift of the E 1/2 value by 0.410 V in 1′Np C relative to the corresponding 3,3′‐di‐ tert ‐butyl‐1,1′‐bis(neopentylamino)ferrocene precursor ( E 1/2 =−0.720 V) indicates sizable electron donation of the amino substituents to the carbene carbon atom, thus rendering oxidation less facile . With the availability of the present new compounds, it was of great interest to study the effect of the nature of the divalent tetrel atom on the electrochemical properties.…”
Section: Resultsmentioning
confidence: 99%
“…Previous electrochemical studies have revealed that the ferrocenylene backbone endows ferrocene‐derived NHCs with reversible electrochemistry, as exemplified for the 3,3′‐di‐ tert ‐butyl‐substituted compound [Fe{(η 5 ‐ t Bu‐C 5 H 3 )NNp} 2 C:] ( 1′Np C). The rather low half‐wave potential ( E 1/2 ) of −0.310 V (vs. ferrocene/ferrocenium) for the 0/+ couple of 1′Np C shows these unusual ferrocene compounds to be rather electron rich . DFT calculations indicate an appreciable delocalisation of the charge and spin density onto the carbene centre for the oxidised form .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations